Adherence to Mediterranean diet and its association with multiple colonic polyps of unknown origin: a case-control study - Bujanda-Miguel, Gabriela; Martínez-Roca, Alejandro; García-Heredia, Anabel; Guill-Berbegal, David; Roche, Enrique; Jover, Rodrigo (Frontiers in Nutrition, 2023)
Multiple colonic polyps do not have a genetic origin in most patients, and the cause of this phenotype remains elusive. Environmental factors, such as diet, could be related to this phenotype. Our aim was to investigate the relationship between the adherence to Mediterranean diet and multiple colonic polyps of unknown origin. A case-control pilot study was carried out with a sample of 38 individuals, including 23 cases with more than 10 adenomatous or serrated polyps from the national multicenter project EPIPOLIP and 15 healthy controls with normal colonoscopy. A validated Spanish version of the MEDAS questionnaire was administered to cases and controls. Adherence to Mediterranean diet was higher in controls than in patients with multiple colonic polyps (MEDAS score: 8.6±1.4 vs. 7.0±1.6; p=0.01). Optimal overall adherence to the Mediterranean diet pattern was significantly higher among the controls than among cases (MEDAS score >9: 46% vs. 13%; OR 0.17; 95% CI 0.03-0.83). Non-optimal adherence to the Mediterranean diet acts as a risk factor for developing colorectal cancer derived from colorectal polyps. Our results suggest that environmental factors play a role in the pathogenesis of this phenotype.